Effects of pharmacogenomics-guided treatment on medication adherence and the antidepressant switching rate in major depressive disorder - Chen, Chaoli; Lun, Yang; Yu, Jing; Zhao, Xiaochuan; Su, Shi; Zhao, Mengqiang; Yan, Yuhang; Wang, Jiaqi; Fu, Ran; An, Feiyue; Duan, Liguang; Yan, Leting; et al. (Frontiers in Pharmacology, 2024)
Background In the treatment of depression, medication plays a crucial role. However, insufficient patient adherence to medication often results in unsatisfactory treatment outcomes, increasing both the recurrence and rehospitalization rates of depression, and consequently imposing a greater economic burden on the healthcare system. Objectives Our objective was to examine the impact of pharmacogenomic testing on medication adherence and antidepressant switching rates among individuals diagnosed with depression. Methods This retrospective cohort study encompassed patients diagnosed with depression who were admitted to the First Hospital of Hebei Medical University between April 2022 and September 2023. Patients were categorized into a pharmacogenomics-guided treatment (PGxT) group and a treatment as usual (TAU) group based on whether pharmacogenetic testing was conducted. The primary outcome measures included the proportion of patients exhibiting medication adherence greater than 80% at three and 6 months post-discharge, as well as the proportion of patients experiencing changes in their prescribed medication types. Results A total of 310 patients in the PGxT group and TAU group were obtained through propensity score matching. Among the 620 patients in both groups, 57.42% demonstrated good adherence (≥80%) at 3 months; this percentage dropped to 31.45% at 6 months. At 3 months of observation, the percentages of patients demonstrating good adherence were significantly different between the groups (64.52% in the PGxT group vs. 50.32% in the TAU group; p < 0.001). The difference was also significant after 6 months (38.06% in the PGxT group vs. 24.84% in the TAU group; p < 0.001). Furthermore, patients receiving PGxT (20.64%) exhibited a lower rate of antidepressant conversion compared to those receiving TAU (31.29%). Conclusion The findings of this study indicate that pharmacogenomics testing positively influences treatment adherence and may decrease the need to switch medications among patients with depression.